Modernism in practice : an introduction to postwar Japanese poetry - Morton, Leith (University of Hawaiʻi Press, 2004)
Postwar modernist verse has been rarely discussed in English-language works on Japanese literature, despite the fact that it has been the dominant mode of poetic expression in Japan since World War II. Now readers of modern Japanese poetry in translation have gained an impressive intellectual and linguistic companion in their enjoyment of modern Japanese verse. Modernism in Practice combines close readings of individual Japanese postwar poets and poetry with historical and critical analysis. Five of the seven chapters concentrate on the life and work of such outstanding poets as Soh Sakon, Ishigaki Rin, Ito Hiromi, Asabuki Ryoji, and Tanikawa Shuntaro. Several of these writers have only come into prominence in recent decades, so this work also serves to acquaint readers with contemporary Japanese verse. A significant dimension of this volume is the detailed and extensive treatment afforded two important areas of postwar Japanese verse: the poetry of women and of Okinawa. Modernism in Practice is noteworthy not only as an introduction to postwar Japanese poets and their times, but also for the numerous poems that appear in translation throughout the volume--many for the first time in book form.